Degradation Kinetics of Antifouling Biocides in Sediment During the Spiking Equilibrium Phase - Campos, Bruno Galvão de; Perina, Fernando Cesar; Abreu, Fiamma Eugênia Lemos; Fillmann, Gilberto; Abessa, Denis M. de S. (Ecotoxicology and Environmental Contamination, 2024)
The new generation of antifouling biocides, as well as other emerging contaminants, has not yet been included in sediment quality guidelines or present standard protocols for sediment spiking. Most of these biocides have short half-lives in water, but little information is available regarding their degradation in sediments. Thus, there is a need to establish a reliable duration of the equilibrium phase for sediment spiking prior to sediment toxicity testing to determine the actual exposure concentrations during ecotoxicological tests. This study aimed to evaluate the degradation of DCOIT, Irgarol, Diuron, and Dichlofluanid during a spiking equilibrium phase of 24 h at three different time intervals (0, 6, and 24 h) and concentrations (10, 100, and 1000 ng g-1), by applying kinetic degradation models. The models presented a better fit for the 1000 ng g-1 treatments, in which the half-lives of DCOIT and Diuron were < 5 h, Dichlofluanid < 2 h, and Irgarol < 6h. Our results also indicate that, except for Dichlofluanid, the degradation rates of the other antifouling biocides were reduced dramatically after 6 h of equilibrium. Therefore, an equilibrium phase of 24 h (or greater than 6 h) was considered viable for sediment spiking. Our findings provide valuable information to guide future sediment toxicity tests using these compounds.